ICT: A STRATEGIC LEVER FOR BUILDING A KNOWLEDGE ECONOMY - State Planning Board, Government of Kerala
The state of Kerala despite being a leader in infrastructure environment, its ability for people to read and use phones and computers has not been able to transform into an ICT powerhouse like its more famous Southern neighbours. The Kerala Perspective Plan 2030 is proposing that the state is to become a knowledge economy where ICT is the lynchpin. Digital technologies will be used to drive productivity and create new growth opportunities across the whole economy. It will catapult Kerala into a league of major knowledge economies by enabling digitalisation of information. ICT will converge with other sectors in an innovative fashion in the economy. Delivery of citizen-centric e-Governance, health and education hubs, smart cities and villages, intelligent transport systems, applications of ICT in agriculture, land zoning are all but just few mention of applications of ICT in the new knowledge economy. E-waste management policy and privacy policies will need to be implemented. Standards need to be defined and continuous monitoring of quantity and quality is required for to build an inclusive society facilitated by ICT.